Defect Engineering of Photocatalysts for Solar Energy Conversion. Issue 4 (29th January 2020) - Ran, Lei; Hou, Jungang; Cao, Shuyan; Li, Zhuwei; Zhang, Yanting; Wu, Yunzhen; Zhang, Bo; Zhai, Panlong; Sun, Licheng
Abstract : Solar energy conversion is one of the most versatile approaches for sustainable energy demands. The fundamental limitations for photocatalysis remain light absorption, charge separation, and photocatalytic (PC) performance of the catalysts. For the past few decades, defect engineering has been proven to be a promising solution for converting solar energy to chemical energy. In this regard, the recent progress of defect engineering toward solar energy conversion is summarized. Beginning with defects classification, the definition of various defects, synthesized strategies, and characterization techniques of controllable material defects are presented. The role of defect engineering on solar energy conversion is developed, extending light absorption, promoting charge separation, and facilitating stable PC reaction. The achievement of the defective photocatalysts is discussed toward versatile applications such as solar water splitting, CO2 reduction, nitrogen fixation, molecular activation, pollutants degradation, and solar cells. Finally, this Review, with regards to defect engineering, ends with the future opportunities and challenges for this exciting and emerging area for solar energy conversion. Abstract : Defect engineering is proven to be a promising solution for photocatalysts for converting solar energy to chemical energy. Herein, it is intended to provide an in‐depth understanding of the tunable defects, synthesized strategies, and characterization techniques of the controllable defects and highlight the roles of defect engineering upon solar energy application in this rapidly developing field.